Effectiveness and safety of using a novel endothelial damage inhibitor in arteriovenous fistula formation - Khalil, Emced; Akalın, Çağrı (Journal of Surgery and Medicine, 2020)
Aim: Patients with end-stage renal disease need accurate and effective vascular access for hemodialysis. Although renal transplantation is the golden standard treatment that provides a life without hemodialysis, an arteriovenous (AV) fistula is the most frequent method for sustaining long-term hemodialysis because of insufficient renal donors. In the current study, we aimed to compare patency rates of AV fistulae created with or without the endothelial protection solution. Methods: This single-center case-control study was conducted between August 2018 and August 2019. Patients with end-stage renal disease requiring AV fistula access for hemodialysis (n= 49) were included in the study and divided into two groups. During the creation of an AV fistulae, endothelial protection solution was used in 27 patients, who constituted Group A, and not used in 22 patients, who were included in Group B (the control group). All fistulae anastomoses were performed by the same surgical team. The demographical data, maturation time, mean flow volume, complications, basal metabolism index (BMI), and patency rates at the 3rd and 6th months were compared. Results: There was no significant difference between the two groups regarding demographical findings (p>0.05). The patency rates were higher in group A at both the 3rd and 6th months (96% and 93%) when compared with group B (64% and 27%) (P<0.05). Conclusion: AV fistulae created with endothelial protection solution has higher patency rates compared to conventionally created AV fistulae.